Perceived Usefulness and Ease of Use as Predictors of Early-year Lawyers Satisfaction with Law Pavilion Electronic Law Reports - Ismail Olatunji Adeyemi; Abdulwahab Olanrewaju Issa (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2020)
This study examined perceived usefulness and ease of use as predictors of early-year lawyers’ satisfaction with Law Pavilion Electronic Law Reports (LPELR). Descriptive survey design was adopted and questionnaire was the instrument used to collect data. Total population sampling was adopted to select sample size. A total of 300 copies of questionnaires were administered on the respondents. However, only 248 copies were returned completely filled and validated for the study. The Cronbach alpha reliability for the study is 0.782. It was found that there is strong positive relationship between perceived ease of use and perceived satisfaction and that there is positive relationship between perceived usefulness and perceived satisfaction. The study findings show that electronic law reports are easy to use and useful for early-year lawyers in their legal research. The study concludes that, as much as the law profession is conservative in nature, the use of e-law reports is making inroads to the profession. It was recommended that technical service provision by LPELR should be improved significantly. Above all, electronic law reports licensors should ensure that task importance of electronic law reports is given utmost consideration when they are designing the system qualities of e-law reports.